STUDY OF MEAN VELOCITY PROFILE AND BOTTOM SHEAR STRESS IN THE AREA AROUND MANGROVE (CASE STUDY: ENDER RIVER ESTUARY, CIREBON REGENCY) - Rizky Hidayat, Alfiansyah
The existence of mangrove ecosystems plays an important role in maintaining the balance of coastal ecosystems, including in mitigating abrasion and capturing sediment. However, the dynamics of currents and bottom shear stress in the area around mangroves are often not well understood, even though this is important for the conservation and rehabilitation of these ecosystems. This study aims to examine the average current velocity profile and bottom shear stress values in the Ender River Estuary, Cirebon Regency, using an Acoustic Doppler Velocimetry (ADV) device. Measurements were carried out for 7 days to obtain current velocity data which were then processed using various methods, such as LP, LP-Max, TKE, MTKE, and RS. The results showed that the current speed around the mangrove area tends to be influenced by tidal conditions, with higher current speeds recorded at high tide. The analysis of bottom shear stress showed significant variations in values between the methods used, with the TKE method providing the most accurate and consistent results. This study also found that the mangrove area has a fairly large bottom shear stress, which plays an important role in binding sediment and reducing current speed. These findings are expected to be the basis for further research in overcoming the problems of sedimentation and shallowing in the Ender River estuary.